2013
DOI: 10.1007/s12012-013-9232-0
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin, 3′-Deoxyadenosine, Prevents Rat Hearts from Ischemia/Reperfusion Injury Via Activation of Akt/GSK-3β/p70S6K Signaling Pathway and HO-1 Expression

Abstract: Cordycepin (3'-deoxyadenosine) isolated from Cordyceps militaris, a species of the fungal genus Cordyceps, has been shown to exhibit many pharmacological functions, such as anticancer, anti-inflammatory, and antioxidant activities. In this study, we investigated the preventive role of cordycepin in ischemic/reperfusion (I/R) injury of isolated rat hearts and anesthetized rats. After Sprague-Dawley rats received cordycepin (3, 10, and 30 mg/kg) or control (0.5 % carboxyl methylcellulose) orally once a day for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…For many years, cordycepin has been applied for various medical purposes, including anti-oxidative stress [39], enhancing bone mineral density [18], preventing myocardial ischemia/reperfusion injury [40], alleviating alcoholic hepatotoxicity [41] and protecting neurons against toxic agents [42]. However, whether cordycepin could exert sufficient protective effects on alcohol-induced ONFH has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, cordycepin has been applied for various medical purposes, including anti-oxidative stress [39], enhancing bone mineral density [18], preventing myocardial ischemia/reperfusion injury [40], alleviating alcoholic hepatotoxicity [41] and protecting neurons against toxic agents [42]. However, whether cordycepin could exert sufficient protective effects on alcohol-induced ONFH has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al investigated the effects of cordycepin in prevention of focal cerebral ischemic/reperfusion (IR) injury and suggested that cordycepin has a neuroprotective effect in the ischemic brain, which is due to the inhibition of inflammation and increase of antioxidants activity related to lesion pathogenesis [ 23 , 24 ]. So cordycepin could be an attractive therapeutic candidate with oral activity against I/R-associated heart diseases such as myocardial infarction [ 25 ]. Besides, cordycepin showed the obvious analgesic effect through acetic acid-induced abdominal constrictions, hot-plate test, and neurolysin inhibition assay in mice [ 26 ].…”
Section: Chemical Constituents and Their Corresponding Pharmacologmentioning
confidence: 99%
“…In addition, the present study also determined that blockade of the autocrine IGF-1 reduced the expression of p-P70S6K. P70S6K is a serine/threonine kinase that contributes to the downstream signaling in the PI3K/Akt//GSK-3β pathway (32). P70S6K may promote cell cycle progression and cell growth through regulating the organization of cytoskeleton (33).…”
Section: Discussionmentioning
confidence: 54%